Maquiavel: Realismo político e ética republicana - Guimaraes, Carlos Nunes (2013)
This thesis deals with the relationship between republican ethics and political realism in Machiavelli s thought and it develops itself through a historical-conceptual approach, considering, in first place, Machiavelli in the context of his time and republican civic humanism. Despite the continuity with tradition, The Prince represents a radical novelty that Machiavelli introduces regarding the council manuals to the Princes; a tradition that a Machiavelli s contemporary, as Erasmus of Rotterdam, still maintains and cultivates in his work Education of a Christian Prince . If Erasmus gives advice to the prince to behave as a good Christian, Girolamo Savonarola, another contemporary that Machiavelli knows and analyzes closely with a blend of skepticism and admiration - calling him " unarmed prophet " - seeks to demonstrate in practice that it s possible to govern a city with the pater noster and the rosary in hands in opposite to Cosimo de Medici s realistic maxim that was resumed centuries later by Max Weber. The confrontation with Erasmus and Savonarola offers the opportunity to analyze the importance that Machiavelli attributes to religion in its relation to politics, starting from the critics to the christian religion and the praise of ancient roman religion. Then an interpretation of the author's thought is built from the perspective of political realism which offers a new analysis of the conflict, arguing that these clashes of humors are responsible for freedom and balance of the politic body. Finally, the thesis addresses its central theme: the relationship between ethics and politics in Machiavelli s thought considering various and contrasting readings of important specialists on this issue. The conclusion shows that, according to Machiavelli, politics is not merely a technical, cold and calculated praxis, but that it carries a value, and it is committed to a greater good which should be reached even if it would be necessary use means that break away from the traditionally accepted moral norms. Therefore Machiavelli seeks an effective policy to achieve the republican purposes: common good and freedom of citizens.